ANALISIS KANDUNGAN RHODAMIN B DAN PEMANIS BUATAN (SAKARIN) PADA BUAH SEMANGKA (CITRULLUS LANATUS) YANG DIJUAL DI PASAR TRADISIONAL DAN PASAR MODEREN KOTA MEDAN TAHUN 2013 - Ike Bena Lestina; indra cahaya; Irnawati Marsaulina (Lingkungan dan Kesehatan Kerja, 2013)
The analysis of Rhodamin B and Artificial Sweetener (saccharin) in watermelon (Citrullus Lanatus) which is sold at traditional and modern market, Medan 2013. Watermelon (Citrullus Lanatus) is very refreshing when enjoyed during the hot day that can be used as thirst remover. Besides refreshing, this fruit is also so beneficial for health. Currently, injection watermelon spreads increasingly. Injection watermelon is watermelon that have been manipulated with textile dyes and artificial sweeteners to attract consumers, and this has been found in several major cities in Indonesia. The aim of this research to determine the presence of dyes (Rhodamine B) and artificial sweeteners (Saccharin) in watermelon which is sold at several markets in Medan. The method of this research was a descriptive survey. Samples were obtained from watermelon farmers in Naga Timbul village, Tanjung Morawa, traditional markets (Sukarame Market, Pringgan Market, Simpang Limun Market, Sentra Market) and modern markets (Carrefour Medan Fair Supermarket, Brastagi Supermarket, Hypermart Sun Plaza Supermarket, Ramayana Aksara Supermarket). Then the samples were analized in Regional Health Laboratories of North Sumatra Province. The analysis carried out by coloring paper chromatography and gravimetric methods. The analysis saccharin sweetener using dried vaporized method.The results of this research from 10 samples of watermelon indicate that they did not use Rhodamine B and Saccharin.It is suggested to Food and Drug Administration (BPOM) to make an inspection of watermelon throughout market in Medan and socializing both to producers and consumers about the use of dyes and artificial sweeteners in order that watermelons which is sold in market being safe and qualify. Keywords : watermelon, rhodamine B, colorant, saccharin, market